Cross national comparison of medical students' attitudes and beliefs about medical cannabis and its application for pain management - Surinporn Likhitsathian; Offer E. Edelstein; Manit Srisurapanont; Yuval Zolotov; Nuntaporn Karawekpanyawong; Alexander Reznik; Richard Isralowitz (Elsevier, 2021)
Objectives: To examine attitudes and beliefs about medical cannabis (MC), and specifically about its application for pain management, across medical students in Israel and Thailand. Design: Cross-sectional survey which measured attitudes and beliefs about MC. Participants were additionally asked to rate the perceived efficacy of MC for different medical conditions that are related to pain (arthritis, chronic pain, fibromyalgia and multiple sclerosis). Pearson's Chi-squared test was used to compare between students from the participating universities. Results: 430 medical students participated, 37.9 % (n = 163) from Israel and 62.1 % (n = 267) from Thailand. Personal cannabis use was reported by 55.6 % of the Israeli and only by 6.9 % of the Thai students (p < .001). Israeli secular students, compared to those from Thailand, were more likely to recommend MC for patient treatment, less concerned about serious physical and mental health risks, and more inclined to support legalization of recreational cannabis. Israeli students reported more permissive attitudes toward MC, but reported feeling less prepared to answer patient/client questions about MC than their Thai counterparts. Conclusions: The findings of this study accentuate the need for curriculum designed around MC use to promote students' preparedness to serve patients in pain or with other medical conditions that may benefit from MC use.